The Protecting Activity of RIPACUT®: A New Therapeutic Approach Preserving Epithelial Health Based on the Combination of Iceland Lichen Extract, Silver Salt, and Sodium Hyaluronate - Raffaella Belvedere; Nunzia Novizio; Daniela Eletto; Amalia Porta; Umberto Di Maio; Antonello Petrella (Life, 2023)
Epithelial integrity and function must be maintained in a dynamic healthy equilibrium, keeping unaltered the oxidative and inflammatory conditions and the microbiome of the cutaneous layers. Beside the skin, other mucous membranes can be injured, such as the nasal and anal ones, because of the contact with the external environment. Here, we detected the effects of RIPACUT®, a combination of Iceland lichen extract, silver salt and sodium hyaluronate that individually act in diverse biological ways. The findings we obtained on keratinocytes, nasal and intestinal epithelial cells reveal that this combination showed a marked antioxidant activity, further assessed by the DPPH assay. Additionally, by analyzing the release of the IL-1β, TNF-α and IL-6 cytokines, we proved the anti-inflammatory effect of RIPACUT®. In both cases, the main preserving action was due to Iceland lichen. We also observed a notable antimicrobial activity mediated by the silver compound. These data suggest that RIPACUT® could signify the basis for an attractive pharmacological approach to maintaining healthy epithelial conditions. Interestingly, this may be extended to the nasal and anal areas where it protects against oxidative, inflammatory and infectious insults. Thus, these outcomes encourage the creation of sprays or creams for which sodium hyaluronate can guarantee a surface film-forming effect.